2015
DOI: 10.1038/ijo.2015.234
|View full text |Cite
|
Sign up to set email alerts
|

Food advertising, children’s food choices and obesity: interplay of cognitive defences and product evaluation: an experimental study

Abstract: The problem of consumption of less healthy foods is complex and multiple factors need to be considered by health practitioners, social marketers and parents to address the issue of childhood obesity. Nutritional knowledge alone is not sufficient to ensure children make healthier food choices and emphasis should also be placed on persuasion knowledge education, targeting of peer norms, self-efficacy and stricter regulation of advertising aimed at children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
1
20
0
2
Order By: Relevance
“…Selain anak menjadi cenderung kurang aktif/sedentari, remaja juga menjadi terpapar iklan yang tinggi dimana 98% produk makanan yang banyak muncul di iklan televisi adalah makanan yang tinggi lemak, gula, dan garam (9). Di samping itu, produk-produk makanan untuk anak-anak juga menarik konsumen dengan berbagai macam strategi marketing preferensi atau kesukaan pada makanan sehingga remaja tertarik untuk membeli dan mengkonsumsi makanan tersebut (10).…”
Section: Kata Kunciunclassified
See 1 more Smart Citation
“…Selain anak menjadi cenderung kurang aktif/sedentari, remaja juga menjadi terpapar iklan yang tinggi dimana 98% produk makanan yang banyak muncul di iklan televisi adalah makanan yang tinggi lemak, gula, dan garam (9). Di samping itu, produk-produk makanan untuk anak-anak juga menarik konsumen dengan berbagai macam strategi marketing preferensi atau kesukaan pada makanan sehingga remaja tertarik untuk membeli dan mengkonsumsi makanan tersebut (10).…”
Section: Kata Kunciunclassified
“…Biasanya produk yang ditawarkan pada iklan berupa makanan dengan tinggi kandungan energi. Anak dengan terpapar iklan akan memiliki kecenderungan mengkonsumsi makanan yang diiklankan tersebut sehingga anak yang terpapar iklan makanan dan minuman di televisi akan memiliki asupan energi lebih tinggi daripada yang tidak terpapar (10).…”
Section: Pembahasanunclassified
“…However, toy premiums are known to encourage purchase and choice, rather than stimulate consumption once the product is obtained [33,76]. Further, an Australian study (n=354, 7-13 years) which explored the effect of a pop-up Internet advertisement on children's subsequent snack choice found that although exposed children chose the advertised food more frequently than the control group, differences did not reach significance [82]. Further analysis revealed a significant result (p<0.001) in a subset of children who had low nutrition knowledge and were hedonism-oriented, with obese children more likely to belong to this group (p=0.037).…”
Section: Experimental Studies Using Premium Offersmentioning
confidence: 99%
“…Significant positive associations were seen in observational studies across a range of populations and countries, using a variety of instruments and methods to measure exposures to marketing and food behaviours in children aged 3-18 years [47-51, 80, 81]. Similarly, experimental studies have shown significant effects from exposure to TV advertising, Internet advergames, product placement, branding and premium offers on children's food preferences, choices and short term food consumption in children aged 3-12 in a variety of different populations [28,29,82]. These results have been demonstrated consistently across heterogeneity of study designs: within-and between-subjects; varying lengths of advertising exposure; and in a large variety of conditions and settings.…”
Section: Experimental Studies Using Premium Offersmentioning
confidence: 99%
“…The lack of effectiveness relating to the prevention of obesity in most behaviour studies is due to the complexity of food consumption behaviour. There are important factors that influence adolescents' eating habits (37) , such as family environment (which we tried to include), friends and the media. In the present study, the intervention strategy based on physical activity was successful although with no impact on the reduction of weight gain, and change was small as expected.…”
Section: Controlmentioning
confidence: 99%